Pengaruh Pengendalian Internal, Moralitas Individu, Ketaatan Aturan Akuntansi Terhadap Kecenderungan Kecurangan Akuntansi - Christy, Lovena; Christy Susanto, Lovena; Carolina, Yenni (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2022)
In Indonesia, the issue of accounting corruption and fraud is still a serious problem because cases of accounting corruption and fraud continue to increase every year. This study was made to examine the effect of internal control, individual morality, and obedience to accounting rules on the tendency of accounting fraud. This research was conducted at a service company in the city of Bandung. One hundred respondents participated in this study. The results of this study indicate that internal control, individual morality, and obedience to accounting rules have a significant negative effect on the tendency of accounting fraud. This study aims to contribute to companies to overcome these problems both in theory and practice. This study provides contributions related to internal control, individual morality, compliance with accounting rules, and the tendency of accounting fraud. Furthermore, for service companies in the city of Bandung, this research can be used to prevent accounting fraud.